Modification of the magnetic mineralogy in basalts due to fluid-rock interactions in a high-temperature geothermal system (Krafla, Iceland) - Oliva-Urcia, Belén; Kontny, Agnes; Vahle, Carsten; Schleicher, Anja M. (Geophysical Journal International, 2011)
Active high-temperature (>150 °C) geothermal areas like the Krafla caldera, NE-Iceland, often show distinct magnetic lows in aeromagnetic anomaly maps suggesting a destruction of magnetic minerals by hydrothermal activity. The main alteration processes in such an environment are low-temperature oxidation (<350 °C, maghemitization) and fluid–rock interactions. We investigated the rock magnetic properties [natural remanent magnetization (NRM) magnetic susceptibility and their temperature and field variation] and the mineralogy, using X-ray diffraction, microscopic methods and electron microprobe analyses, of two drill cores (KH1 and KH3) from the rim of the Krafla caldera. The drill cores have distinctly lower NRM values (average <3 A m−1) compared to younger surface basalts (average 20 A m−1) along with a large variation in magnetic susceptibility (1.3 × 10−7– 4.9 × 10−5 m3 kg−1). The secondary mineral assemblage (sulphides, sphene, rutile and chlorite) indicates an alteration within the chlorite–smectite zone for both cores without depth zoning. Optical miscroscopy in combination with the Bitter technique and backscatter electron microscopy along with the thermomagnetic analyses allow distinguishing two different magnetomineralogical groups of titanomaghemite: (1) titanomaghemite with intermediate titanium concentration and probably high vacancy concentration, and (2) titanomaghemite with low titanium concentration and low vacancy concentration. The mineral assemblages, textures and magnetic properties deduced from the mentioned magnetic measurements indicate two-stage transformation mechanism: (1) Dissolution of titanium at low pH under oxidizing conditions. The ulvöspinel component of titanomagnetite and ilmenite forms rutile or sphene, and Fe2 + migrates out of the spinel lattice forming titanomaghemite. (2) Formation of pyrite and dissolution of remaining titanomaghemite under reducing and acidic conditions. The latter mechanism produces ghost textures (all titanomaghemite is transformed and only ...